2003
DOI: 10.1029/2002ja009442
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence frequencies of IMF triggered and nontriggered substorms

Abstract: [1] The occurrence of triggered and nontriggered substorm are examined in light of current interest in such issues as substorm identification, IMF B y variations, and potentially undetected small-scale solar wind perturbation. Global substorms are identified using a sudden, persistent decrease in the AL index. The onset of this global expansion is taken to be the time of the Pi 2 burst nearest in time to the beginning of the AL decrease. IMF triggers were identified both subjectively through visual scanning of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
119
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(139 citation statements)
references
References 26 publications
15
119
3
Order By: Relevance
“…That approach gives a good global estimate for the substorm onset. This does not hold for all substorms since some substorms occur during northward IMF (Hsu and McPherron, 2003;Kullen and Karlsson, 2004). All three substorms of the present study are associated with more typical southward IMF conditions.…”
Section: Event and Data Descriptionsmentioning
confidence: 76%
See 1 more Smart Citation
“…That approach gives a good global estimate for the substorm onset. This does not hold for all substorms since some substorms occur during northward IMF (Hsu and McPherron, 2003;Kullen and Karlsson, 2004). All three substorms of the present study are associated with more typical southward IMF conditions.…”
Section: Event and Data Descriptionsmentioning
confidence: 76%
“…In the solar wind we observed a change in sign of the IMF B Y component, an increase in magnitude of IMF and abruptly decreasing solar wind dynamic pressure, which is a signature of a stream interface (Gosling et al, 1978). The studies by Hsu and McPherron (2003) and Kullen et al (2010) show that 50-60 % of the substorms are associated with a potential IMF B Z or B Y trigger. Furthermore, large changes in the dynamic pressure (>7 nPa) are only responsible for a fraction (1-3 %) the largest substorms.…”
Section: Event Summary and Discussionmentioning
confidence: 86%
“…The sudden increase of the AE index is usually used as the substorm onset signature by many researchers (e.g., Hsu and McPherron, 2003;Huang, 2005). From this study on substorm, we found that the time of sharp increase of AE index was within the substorm expansion phase, not at the substorm onset time.…”
Section: Discussionmentioning
confidence: 66%
“…The commonly accepted idea is that substorms are triggered by geoeffective changes in the solar wind parameters. The alternative concept suggests that substorms can be triggered by internal process (Hsu and McPherron 2003;Liu et al 2011;McPherron et al 1986). Indeed, occurrence of moderate and even intense substorms under conditions of relatively steady interplanetary (northward) magnetic field was noted in many studies (e.g., (Kullen and Karlsson 2004;Lee et al 2007;Wu et al 2002)).…”
Section: Discussionmentioning
confidence: 99%